INTEGRATION OF PROJECT BASED LEARNING ETHNOSAINS TENUN IKAT TO IMPROVE UNDERSTANDING OF SCIENCE CONCEPTS AND CREATIVE THINKING STUDENTS JUNIOR HIGH SCHOOL (SMP) TANIMBAR - Rupilele, Edy; Mahulette, Ferymon; Papilaya, Pamella Mercy (Universitas Pattimura, 2021)
This study aims to determine increased understanding of the concept of science through the integration of ethnoscience tenun ikat project based learning at SMP tanimbar, improving the ability to think creatively through the integration of the ethnoscience, differences in understanding the concept of science through the integration of project based learning ethnoscience, and differences in the ability to think creatively through the integration of ethnoscience. This research was conducted on April 26 – June 26 2021 located at SMPN 3 Wuarlabobar, SMPN 3 Waturu, SMP Christen Batuputih, SMPN 1 Atap Wermatang. The research design used a quasi-experimental design used two groups, namely the experimental group and the control group. The results of the study show that the integration of project based learning into the learning process can improve understanding of science concepts and ability to think creatively. The conclusion of this study is that there is a significant difference in the value of understanding science concepts and students' creative thinking ability between the sample groups of SMP Negeri 3 Wuarlabobar, SMP Negeri 3 Waturu, SMP Christen Batuputih and SMP 1 Atap Wertmatang.